Influence of particle shape on the shear strength and dilation of sand-woven geotextile interfaces - Afzali-Nejad, Aliyeh; Lashkari, Ali; Shourijeh, Piltan Tabatabaie (Geotextiles and geomembranes, 2017)
The influence of particle shape on the mechanical behavior of sand-woven geotextile interfaces over a wide domain of soil density and normal stress is studied. A uniformly graded angular fine sand, and a blend of well rounded glass beads with identical particle size distributions, were selected as granular material. Experiments revealed the impact of particle shape on peak and residual friction angles as well as the maximum dilation angle of interfaces between both granular media and woven geotextile. It was observed that the residual friction angles of interfaces between angular sand/glass-beads and woven geotextile are very similar to the residual friction angles of angular sand and glass-beads in soil–soil direct shear test. It is understood that the peak friction angle and maximum dilation angle of angular sand-woven geotextile were slightly lower than corresponding values for angular sand in soil–soil direct shear test. While the peak friction angle and maximum dilation angle of angular sand-woven geotextile interface decrease with the increase in normal stress, experiments showed that these factors are insensitive to normal stress for glass beads-woven geotextile interfaces, at least for the range studied herein. All interfaces with woven geotextile as the contact surface exhibit an abrupt loss of shear strength in the post-peak regime of behavior. Finally, a unified stress-dilation law for the angular sand-woven geotextile, glass beads-woven geotextile, and angular sand-roughened steel interfaces is obtained.